2018
DOI: 10.1002/mc.22777
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy potentiates the anti‐metastasis effect of phenethyl isothiocyanate through JAK2/STAT3 pathway in lung cancer cells

Abstract: Phenethyl isothiocyanate (PEITC) is a natural compound abundant in cruciferous vegetables. PEITC possesses anti-tumor effect in various human malignances. Our previous study has shown that benzyl isothiocyanates (BITC) induce autophagy in lung cancer cells. However, whether autophagy play a role in the inhibitory effect of PEITC on lung cancer metastasis is unclear. In this study, we found that PEITC suppressed migration and invasion of lung cancer cells by regulating MMP2. It also induced autophagy, evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…They are believed to inhibit lysosome-dependent autophagy and improve chemo and radio sensitivity [76]. Some of the most recent publications on this matter included breast cancer [77], pancreatic cancer [78,79], lung cancer [80], colon cancer [81], and bladder cancer [82].…”
Section: Quinolines: Chloroquine and Quinidinementioning
confidence: 99%
“…They are believed to inhibit lysosome-dependent autophagy and improve chemo and radio sensitivity [76]. Some of the most recent publications on this matter included breast cancer [77], pancreatic cancer [78,79], lung cancer [80], colon cancer [81], and bladder cancer [82].…”
Section: Quinolines: Chloroquine and Quinidinementioning
confidence: 99%
“…Though, both GSL-rich broccoli and GSL-rich pak choi up-regulated the expression Nrf2 target genes, colitis and tumor were drastically reduced in GSL-rich pak choi diet [ 29 ]. The study in mice with colon cancer showed an anti-inflammatory effect of raw broccoli is higher than the cooked broccoli [ 30 ]. Cruciferous vegetable diet displayed significant tumor regression and reduced tumor occurrence in murine models of colorectal carcinoma [ 31 ].…”
Section: Epidemiological Studies Of Itcsmentioning
confidence: 99%
“…214 Hence, CQ can affect metastatic cells in transition and this can explain the statistically significant effect of CQ against metastatic cancer cells in patients. 217,218 As an example, interactions between NF-jB, STAT3, p53, and the glucocorticoid receptor (GR) guide dynamic transitions in the structures and functions of a cells' organelles and the resulting changes in the cells' phenotype. 216 The capacity of CQ to affect cancer cells in transition can also be linked to the interactions between transcription factors that steer cellular metabolism.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%
“…216 The capacity of CQ to affect cancer cells in transition can also be linked to the interactions between transcription factors that steer cellular metabolism. 217,218 As an example, interactions between NF-jB, STAT3, p53, and the glucocorticoid receptor (GR) guide dynamic transitions in the structures and functions of a cells' organelles and the resulting changes in the cells' phenotype. [219][220][221][222] Organelles, in turn, form intracellular networks that control autophagy and cell death.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%